Analisis Usaha dan Nilai Tambah Pengolahan Dodol Rumput Laut Skala Rumah Tangga di Desa Loon, Kecamatan Kei Kecil, Kabupaten Maluku Tenggara (Business Analysis and Added Value of Processing Dodol Seaweed in Household Scale of Loon Village, Kei Kecil Sub-District, Southeast Maluku District) - Anna Kartika Ngamel (IPB University, 2015)
This study aimed to quantify the value of profit, the value of break-even point, the added value and the ratio of added value to the processing business of dodol seaweed in Loon Village, Kei Kecil Sub-District, Southeast Maluku District. The method used in this study was a survey method with qualitative and quantitative approaches. The location of the research was determined purposively, where the population was the entrepreneur of dodol seaweed in Loon village. The analytical method used was the analysis of profit, break-even and added value Hayami method. The results showed that the business of dodol seaweed deserves to be developed with a profit of Rp 26 118 million,- per year. The cumulative gain value (R/C ratio) was 1.77, which means that the processing business of dodol seaweed was feasible because it meets the eligibility criteria value greater than one. The obtained break-even point value was 1.694 dus, (Rp 11 300) and the cost was Rp 26.97 million. The added value created from each kilogram of dried seaweed was Rp 197 792, with a ratio of 79.12% of the production value. According to Hubeis (1997), this added value ratio is a high added value category that has a ratio of > 40%.Keyword : analysis of profit, break even, added value, dodol seaweed.